Assembly list sheet 12_Rev A - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains structural as-built drawings of steel structure of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.